2004
DOI: 10.1007/s10350-004-0626-8
|View full text |Cite
|
Sign up to set email alerts
|

The Accuracy of Clinical Examination in the Diagnosis of Rectal Intussusception

Abstract: There is no clear relationship between rectal intussusception and constipation. However, intussusception is related to sphincter function and may be of clinical relevance. A normal clinical examination will exclude most long intussusceptions, whereas a positive finding needs further evaluation with defecography.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 20 publications
1
23
0
Order By: Relevance
“…The definition of intussusception was reported and/or referenced in a total of 40/63 (63%) studies. Among these, three main grading systems were used to define the severity of intussusception, originally described as “unilateral or circumferential infolding of the rectum during straining.” A total of seven studies adopted the classification proposed by Shorvon et al, which identifies seven degrees of intussusception, with grades 1‐4 inclusive being intra‐rectal (1 and 2: <3 mm; unilateral or circumferential, respectively; 3 and 4: >3 mm; unilateral or circumferential, respectively), 5 and 6 intra‐anal (the leading edge of the infolding impinges onto or into the anal canal, respectively), and 7 representing an external rectal prolapse.…”
Section: Summary Of Search Results and Study Qualitymentioning
confidence: 99%
“…The definition of intussusception was reported and/or referenced in a total of 40/63 (63%) studies. Among these, three main grading systems were used to define the severity of intussusception, originally described as “unilateral or circumferential infolding of the rectum during straining.” A total of seven studies adopted the classification proposed by Shorvon et al, which identifies seven degrees of intussusception, with grades 1‐4 inclusive being intra‐rectal (1 and 2: <3 mm; unilateral or circumferential, respectively; 3 and 4: >3 mm; unilateral or circumferential, respectively), 5 and 6 intra‐anal (the leading edge of the infolding impinges onto or into the anal canal, respectively), and 7 representing an external rectal prolapse.…”
Section: Summary Of Search Results and Study Qualitymentioning
confidence: 99%
“…Alternatively, chronic IRP can present with faecal incontinence (FI) . It has been postulated that FI associated with IRP is caused by occult defects of the external anal sphincter, traction pudendal neuropathy resulting from repeated excessive straining and distension of the lower rectum by the intussusceptum activating the rectoanal inhibitory reflex and inducing relaxation of the internal anal sphincter causing overflow incontinence .…”
Section: Introductionmentioning
confidence: 99%
“…If this relaxation is absent, the examiner should suspect dyssynergic defecation [11]. A recent cross-sectional study in 127 subjects with functional constipation showed that routine clinical examination can diagnose approximately half of patients with anorectal intussusception and most of the longer intussusceptions (>3 cm) seen at defecography [15]. Although digital rectal examination is an inexpensive and useful clinical tool, knowledge about how to perform a comprehensive evaluation is lacking.…”
Section: Physical Examination and Routine Blood Testsmentioning
confidence: 99%